Brand activation: the process of door- to- door activity of Nestlé Bangladesh Limited (MAGGI Shad e Magic Masala) - Tasnim, Nishat (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.